Transient response improvement of direct current using supplementary control based on ANFIS for rectifier in HVDC - I Made Ginarsa; Agung Budi Muljono; I Made Ari Nrartha; Sultan Sultan (Institute of Advanced Engineering and Science, 2020)
Current control scheme is commonly used in high voltage direct current (HVDC) to transmit power delivery. This scheme is done by adjusting trigger angle to regulate direct current (DC) in thyristor devices. The adaptive neuro-fuzzy inference system (ANFIS) control is widely applied for start and fault operation. But, solution for transient response of DC current in HVDC system is not clearly studied before. In this paper, supplementary control (SC) based on ANFIS is proposed to improve the transient response of the current. The SC control is designed by learning-processes and SC parameters are obtained by data-training automatically. For current reference at 1.05 pu and up-ramp at 20 pu/s, maximum overshoot is achieved at 5.12% and 7.72% for the SC and proportional integral controller (PIC), respectively. When the up-ramp is increased to 28 pu/s, the maximum overshoot is achieved at 10.01% for the SC. While, the peak overshoot for the PIC is 14.28%.